1998
DOI: 10.1159/000055513
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Drug Effects on Cyclic AMP in Cultured Human Trabecular Meshwork Cells

Abstract: Cyclic AMP production in the presence or absence of various adrenergic agonists and antagonists was determined in cultured human trabecular cells using a gammaflow automated radioimmunoassay that allowed multiple simultaneous experiments and reproducible results. Adrenergic agonists and antagonists showed activation and inhibition constants consistent with the presence of β2-receptors: Ka of isoproterenol < epinephrine < norepinephrine < phenylephrine; Ki of timolol < betaxolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…These early studies showed that both timolol (1 mM) and racemic betaxolol (1 mM) inhibited epinephrine-induced cAMP production. Our studies compare favorably with recent published reports showing K i values of 0.8 nM for timolol, and 2 nM for ICI-118551 (21) in cultured primary human TM cells. Interestingly, racemic betaxolol was weaker in these studies (K i 5 850 nM) when compared to our results (K i 5 19 nM).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These early studies showed that both timolol (1 mM) and racemic betaxolol (1 mM) inhibited epinephrine-induced cAMP production. Our studies compare favorably with recent published reports showing K i values of 0.8 nM for timolol, and 2 nM for ICI-118551 (21) in cultured primary human TM cells. Interestingly, racemic betaxolol was weaker in these studies (K i 5 850 nM) when compared to our results (K i 5 19 nM).…”
Section: Discussionsupporting
confidence: 91%
“…yielded a range of potencies (EC 50 values) from 66 6 8 nM for isoproterenol to .10,000 nM for phenylephrine. Our cell growth conditions may have produced a higher receptor density or more efficient coupling to adenylyl cyclase thus allowing for an increased amount of cAMP production and greater sensitivity in the assays than previous studies (12,21). Experiments conducted with cultured primary human ciliary epithelial cells produced a stimulation of cAMP production of 1.4 fold for norepinephrine (1 mM), 2.5 fold for epinephrine (1 mM), and 3.5 fold for isoproterenol (1 mM) above basal values (12).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Long-term use of timolol causes functional and morphological ef-fects on trabecular meshwork cells. [13][14][15][16] Although the clinical effects of timolol on IOP reduction are well established, little is known about the potential effects of timolol on expression of glaucoma genes. If induction of glaucoma genes has the potential to affect disease pathologic features, then it is important to know whether glaucoma medications used to treat patients can affect expression levels of glaucoma gene transcripts or products in relevant tissue types.…”
mentioning
confidence: 99%